2009
DOI: 10.1080/00288230909510526
|View full text |Cite
|
Sign up to set email alerts
|

Soil C and N sequestration and fertility development under land recently converted from plantation forest to pastoral farming

Abstract: Soil organic matter accumulation and concomitant fertility changes in soils recently converted from plantation forest to pastoral agriculture in the Taupo-Rotorua Volcanic Zone have been observed, with a probable soil C sequestration rate of 6.1 t ha-1 year-1 , and a soil N sequestration rate of 0.451 ha-1 year-1 , to 150 mm soil depth, for the first 5 years after conversion attwo of three selected farms. Rapid increases in Olsen P were observed, with soils reaching their optimum agronomic range within 3-5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…New Zealand studies on forest and pasture comparisons on other Soil Orders have also reported greater total C under pastures than under forest or scrub, but those studies generally sampled to much shallower soil depths (Walker et al 1959;Giddens et al 1997;Hedley et al 2009;Schipper and Sparling 2011;Hewitt et al 2012) than used in the current study. There is often greater variability in total C contents of lower soil horizons (Franzluebbers 2009;Kravchenko and Robertson 2011), which can mask changes in the total soil profile, even when changes in the A horizon may be significant (Kravchenko and Robertson 2011;Schipper and Sparling 2011).…”
Section: Total C and N In The Soil Profilementioning
confidence: 68%
See 4 more Smart Citations
“…New Zealand studies on forest and pasture comparisons on other Soil Orders have also reported greater total C under pastures than under forest or scrub, but those studies generally sampled to much shallower soil depths (Walker et al 1959;Giddens et al 1997;Hedley et al 2009;Schipper and Sparling 2011;Hewitt et al 2012) than used in the current study. There is often greater variability in total C contents of lower soil horizons (Franzluebbers 2009;Kravchenko and Robertson 2011), which can mask changes in the total soil profile, even when changes in the A horizon may be significant (Kravchenko and Robertson 2011;Schipper and Sparling 2011).…”
Section: Total C and N In The Soil Profilementioning
confidence: 68%
“…However, the rates of accumulation in our study were slower than some previously reported. Hedley et al (2009) suggested that overall accumulation of total C on Taupo Pumice Soils for the first 5 years after conversion was equivalent to 0.61 kg C m -2 year -1 . In our study, accumulation rates of soil C in the whole profile over the first 10 years after conversion were 0.2 kg C m -1 year -1 at Wairakei and 0.21 kg C m -1 year -1 at Atiamuri, with no significant change at Tokoroa.…”
Section: Rates Of C and N Accumulationmentioning
confidence: 99%
See 3 more Smart Citations